Hybrid Learning In English Language Learning: Students and Teachers Perception - Putri, Galuh Isbiyantari; Lindawati, Rini; Mardiana, Wiwik (Philosophiamundi, 2024)
This research uses the hybrid learning method to discuss the perceptions of students and teachers in English language learning. This study aims to understand how students and teachers perceive English language learning through the hybrid method. This research used a descriptive qualitative method, with data obtained through interviews and questionnaires. The study focuses on students and teachers from the Faculty of Teacher Training and Education, English Department, at Universitas Islam Majapahit. The results of this research indicate that both students and teachers have positive responses toward using hybrid learning in English language education. Hybrid learning facilitates students' understanding of the material, as they can review the instructional videos on the e-learning platform. Students become more enthusiastic about participating in lessons due to the various features and tools available in hybrid learning, which helps to reduce boredom during classes. Hybrid learning is also highly effective in assisting students who cannot attend in person, allowing them to follow the lessons without missing any material. Teachers conduct evaluations at the end of each lesson to identify and address any shortcomings in that day's teaching. Teachers feel glad because this method can accommodate students and teachers who cannot attend in person.